The case of Prunus africana (J.D. Hook): lesson from a non-timber forest product from Mount Cameroon - Schroder, J.M. (2000)
Prunus africana trees' bark from moist forests on Mt. Cameroon produce medicinal extractive that is traded internationally with high economic significance. Because sustainable bark harvesting was widely abandoned since the early 1990s and because the economic status of the rural population has deteriorated in the area, illegal and destructive debarking became common. Under the present form of exploitation this tree species is expected to become extremely scarce in the region within a few years. To understand this recent development, historical, legal, and social conditions of the local populations are highlighted. With regard to these constraints, options for sustainable management of this valuable non-timber forest product are presented on the legal and technical level to maintain a commodity that has a high potential to contribute to the socioeconomic development of the rural people.